RCRA small quantity generators a commitment to the future - Coastal Video Communicatios (Virginia : Coastal Video Communications, 1994)
This video will help you understand RCRA requirements for Small-Quantity Generators (SQGs) and what is expected from you and your employer, but more importantly, it will help everyone in your facility pull together to protect the environment and make a commitment to our future
Keywords: Industries -- Environmental aspects -- United States; Hazardous wastes -- United States -- Management